Assessing the Effect of Community Radio on Rural Development - A Study of Ajumako Bisease Community in Ajumako-Enyan-Essiam District - Agyemang, Afua Koramah (UniMAC-GIJ, 2020)
The study investigated the effect of community radio on rural development using Ajumako Bisease Community in Ajumako-Enyan-Essiam District as a case study. Thirty (30) respondents were selected using convenience and purposive sampling techniques. The study adopted a qualitative research approach in analysing the study findings where semi-structured interview were used to gather primary data. The first objective was to assess the participatory nature of Breezy FM in community development at Ajumako Bisease. The study postulated that majority of community members would be consulted for their views before the establishment of Breezy FM. Also, community members participate in the radio programme through phone-in segments and providing stakeholders meeting with the community for them to bring their views for the development of the community radio. The second objective sought to examine the challenges constraining the growth and sustainability of Breezy FM community radio broadcasting at Ajumako Bisease. The study postulated that the main challenges that would be facing the community radio was inadequate funding, high level of labour turnover, strict regulatory requirement and lack of deep participation from the community members. The last objective was to ascertain the effect of Breezy FM on rural development in Ajumako Bisease. The study ascertained that the community would be benefiting a modern community library, improvement of school enrolment, a community Senior High School, improvement in farming practices and a reduction in teenage pregnancy. Apart from this developmental projects the radio would have also helped the community on the importance of exercising their civic obligation such as paying taxes, levies, tolls, voting and taking part in communal labour. The study further recommends that government, NGOs and other stakeholders ought to collaborate with the Community Radio to bring more development into rural communities.
Thesis